Oestrogen receptors and hypoxia inducible factor 1 alpha expression in abdominal wall endometriosis. Issue 1 (July 2020) - Zhang, Ling; Xiong, Wenqian; Fu, Tian; Long, Xuefeng; Zhang, Zhibing; Liu, Yi; Lv, Gang
Abstract: Research question: What are the protein levels and localization of oestrogen receptors (including ERa, ERb and G protein-coupled oestrogen receptor [GPER]) and hypoxia-inducible factor-1alpha (HIF-1a) in normal control endometrium (COEM) and ectopic endometrium from abdominal wall endometriosis (AWE). Design: AWE ( n  = 20) were obtained during surgery; COEM ( n  = 40) were collected by curettage. All tissues were obtained during the proliferative or secretory phase. Formalin-fixed paraffin-embedded tissues were used for immunohistochemical study for oestrogen receptors and HIF-1a proteins. Result(s): The expression of oestrogen receptors and HIF-1a in AWE differed from that in the corresponding menstrual cycle phase of COEM. Compared with COEM, ERa and HIF-1a were decreased whereas ERb and GPER were increased in AWE. The greatest difference was in GPER, with increased protein expression in both the cytoplasm and nucleus of endometrial epithelial and stromal cells, as well as a distinct change in localization from cytoplasmic expression to nuclear and cytoplasmic expression, compared with COEM. Conclusions: Our data suggest that the expression changes of oestrogen receptors and HIF-1a, especially GPER, are associated with AWE, which may provide new clues to understanding the cause of endometriosis.